Be happy to be successful: a mediational model of PERMA variables. (12th February 2021) - Goh, Pei Shan; Goh, Yong Wah; Jeevanandam, Loshnah; Nyolczas, Zsuzsa; Kun, Agota; Watanabe, Yayoi; Noro, Ikuko; Wang, Rong; Jiang, Jiang
Abstract : To conceptualize how employees' perception of job performance might be generated, the present study tested a process model of Seligman's (2011, The Journal of Positive Psychology 13, 333) PERMA. Hierarchical regression and mediation analyses were conducted on 648 working adults from Hungary, Japan, China and Australia. A significant mediation effect of Positive Relationships and Meaning on the pathway from Positive Emotions to Accomplishment was found. Meaning was a stronger mediator than Positive Relationships. The indirect effect of Engagement as a mediator between Positive Emotions and Accomplishment was not significant, contrary to past empirical evidence of Engagement as a mediator. These findings demonstrate the significance of examining PERMA with a holistic approach. The implications of this study on workplace performance interventions are also discussed.